Analysis of the association between the acetabular morphology and femoral head in children aged 0–3 years with developmental hip dysplasia - Xu, Liukun; Wang, Bo; Wang, Li; Zhang, Zhiqun (Frontiers in Pediatrics, 2023)
The authors declare that no funds, grants, or other support were received during the preparation of this manuscript. with BCEA. After adjusting for age(mo.), BMI, BCEA, and CCEA, BPoAcet and CPoAcet was found to be correlated with the length of the ossifying nucleus ratio.Preoperatively, the CAI, BAxAcet, BPoAcet, CPoAcet, and BTAD were correlated with the height of ossifying nucleus ratio after correcting for age, BMI, BCEA, and CCEA.The measurement parameters of hip socket morphology on MRI are associated with femoral head development, making them potential predictive indicators for femoral head development in DDH patients. These findings offer valuable insights for clinical decisions regarding the timing and approach of surgery in patients with developmental hip dislocation.